Challenges in Treating Genodermatoses: New Therapies at the Horizon - Morren, Marie-Anne; Legius, Eric; Giuliano, Fabienne; Hadj-Rabia, Smail; Hohl, Daniel; Bodemer, Christine (Frontiers in Pharmacology, 2022)
Genodermatoses are rare hereditary diseases involving the skin and frequently other organs, some of them associated with premature lethality, a cancer risk and a poor quality of life. Progress in molecular genetics and translational research unravelling the underlying mechanisms, has opened the way for new treatment strategies for these diseases with high unmet medical needs. Interfering with pathways, disturbed by the encoded proteins, is one option. This means inhibition of signalling in case of overactive pathways, or targeting a pathway disequilibrium when the pathway has become less active. Another possible approach is intervening in inflammatory reactions induced by the altered protein. A more aetiological approach is to correct the defective protein, induced by the underlying genetic defect, or correct the genetic defect itself, therapeutic strategies that are frequently personalised, depending on disease, protein, even on the responsible mutation. Repurposed drugs like aminoglycosides are used as read through strategy for premature termination codons. Sometimes the defective protein can be replaced by a normal functioning one. Cell therapies with allogeneic normal keratinocytes or fibroblasts may restore pathologic skin, systemically administered allogeneic bone marrow or mesenchymal cells may additionally restore other organs affected. Genetic engineering is another rapidly expanding field. Insertion of a normal functioning gene in patients cells or, more recently, genome editing allowing reframing, insertion or deletion of exons or disruption of aberrant functioning genes, have reached the stage of (pre)clinical use. Finally, interfering with gene transcription is another approach reducing the severity of the disease. Most of these strategies are short lasting and have to be administered lifelong. In contrast insertion of a normal gene or correcting the defect by editing may be definitive if it is performed in stem cells. Each technique however has drawbacks, which will be discussed in the paper. Moreover, it is important to stress that gene therapy strategies are most often very expensive. Therefore prevention of disease transmission remains an important goal to be implemented in strategies to deal with genodermatoses. This implies counselling on the disease and reproductive options such as preimplantation genetic testing followed by transfer of a non-affected embryo to the uterus.